Tell el-Dab'a XXII. "Der Mund der beiden Wege". Teil II: Abbildungen-Tafeln-Pläne-Profile-Schnitte Die Siedlung und der Tempelbezirk des Mittleren Reiches von Ezbet Ruschdi - Czerny, Ernst (Verlag der Österreichischen Akademie der Wissenschaften, 2015)
The final and comprehensive publication of the archaeological results of excavations by the Austrian Archaeological Institute at the site of Ezbet Rushdi (area "R/I") within the broader archaeological region of Tell el-Daba in the eastern Nil-delta. A Temple and a settlement site were investigated, both of Middle Kingdom origin.